Analisis Hukum Islam dan Sosial Max Weber terhadap Penggunaan Jasa Wali dalam Pernikahan Sirri di Parakan, Temanggung - Fatatin Nisak; Khoirin Nisa’ (IAI Darussalam, 2021)
This study aims to determine whether the use of guardian services is following Islamic rules and what is the motive of this action based on Max Weber's theory of social action. This type of research is a case study located in Parakan, Temanggung with a qualitative approach. The data collection technique uses documents and interviews with guardian service users. The sources are obtained from primary sources in the form of news from Google and references to Islamic law and Max Weber's theory of social action as secondary sources. The researcher uses descriptive analysis with a deductive mindset. This study concludes that the use of guardian services in cirri marriages here violates several Islamic rules. Among them is using the services of a muhakkam guardian without any clear reason about the lineage guardian. According to Weber, there are four kinds of social actions that become the motive and purpose of using the services of a guardian in Parakan, Temanggung. The goal-oriented social action factor dominates in this case.